Ekonomi Politik Penebas Durian: Strategi Penebas Dalam Mempertahankan Etika Subsistensi - Yoga Septa Nurivandi (Fakultas Ilmu Sosial dan Ilmu Politik, 2026)
The profession of durian middlemen (penebas) in Wonosalam Village plays a critical role as a vital bridge connecting local farmers to the broader market. Known widely as the durian capital of East Java, Wonosalam possesses a distinct economic advantage in plantation agriculture, where durian cultivation serves as the primary livelihood for the majority of its residents. Operating as key liaison actors, these middlemen face high economic risks and vulnerabilities in maintaining their families' well-being. However, such risks are actively mitigated through various strategic actions developed by the local penebas. This phenomenological qualitative study aims to describe and analyze the specific strategies used by these middlemen to uphold their livelihood ethics while navigating potential market threats. Drawing on primary insights from durian farmers and middlemen as key informants, the findings reveal that these actors implement targeted tactical measures to minimize severe economic losses. The primary threats identified include adverse weather conditions that trigger crop failures and unfair competition among middlemen, which risks damaging both the market price and the established reputation of Wonosalam Durian. Ultimately, this study concludes that these intermediaries employ a combination of survival strategies, including exploiting seasonal variations, engaging in occupational multiplicity by taking on multiple professions, and utilizing short- and long-term investments to secure their households' economic stability. To sustain these efforts, a strong synergy between the local government and the community is highly crucial. Such collaboration is essential to regulate competition patterns, ensure regional economic stability, and preserve the Wonosalam Durian brand, all of which play a fundamental role in securing the middlemen's long-term subsistence needs.
The Political Economy of Durian Middlemen: Middlemen's Strategies in Maintaining Subsistence Ethic
:: Finalisasi repositori 14 Juli 2026_Kurnadi
Keywords: Durian; EconomicStrategy; Penebas(middlemen); Subsistence; Wonosalam